Identification of Students Basic Science Process Skills Assisted of Practical Worksheet Based on Multiple Representations (Universitas Negeri Semarang, 2018)
Skills in the learning process are needed by students to be able to shape and develop the character possessed. This study aims to identify basic science process skills of students assisted practical worksheet based on multiple representations as media. This research was conducted by observation method that was done at the time of practicum activity by using an observation sheet and test method with response test. Students did practicum with practical worksheet media equipped with basic science process skills indicator and multiple representation level. Then the students worked the question with the basic science process skill indicators in it. Based on the analysis of the observation result, the basic science process skills profile of students in SMAN 11 Semarang was included in the high criteria with a range of 68 to 84. The criteria for each basic science process skills indicator were also analyzed from practicum 1 and practicum 2 which is high for indicators to observation, classifying, measuring, inferencing, predicting and knowing the relation of numbers and very high for indicators communicating and knowing relation between space and time. It can be concluded that students have demonstrated proficiency profile of basic science process. This research can be used as a reference for teachers and other researchers to improve student’s basic science process skills on different subjects.